Partisipasi dan Pemberdayaan Sumber Daya Lokal Sebagai Upaya Pengurangan Risiko Bencana Berbasis Komunitas di Pidie Jaya Aceh Guna Mendukung Keamanan Nasional - Riskina Tri Januarti; Anisa Nurur Rachmatika; Tri Winugroho; Syamsul Maarif; Adi Subiyanto (PendIPA Journal of Science Education, 2021)
[Participation and Empowerment of Local Resources as Community-Based Disaster Risk Reduction Efforts in the Community of Pidie Jaya District, Aceh Province to Support National Security]. Pidie Jaya District, Aceh Province has geographical conditions that include coastal and mountainous areas as well as the Great Sumatran Fault that stretches from Lampung to the Andaman Sea. This situation makes Pidie Jaya an area prone to disaster risk. Disaster Risk Reduction (DRR) can be a strategy in an effort to reduce vulnerability and increase capacity in disaster-prone areas. This study aims to analyze community-based DRR efforts (CBDRM) which include participation and empowerment of local resources in the community in creating independence in Pidie Jaya District. The subjects in this study were the people of Pidie Jaya Regency. The method used in this research was descriptive qualitative using data sourced from interview data and documentation. Research results from the triangulation process show that the participation and empowerment of the people of Pidie Jaya Regency in Community-Based Disaster Risk Reduction efforts is still not running optimally, but it has increased understanding of disaster science in the area including knowledge, culture, anticipation, and mitigation. The principle of Building Back Better is implemented by the Government of Pidie Jaya, namely by reconstructing the lives of community groups through reducing vulnerability and increasing the ability to avoid risk factors for future disasters. Approaches through religious and dayah leaders take part in providing outreach and education. The result of CBDRM Pidie Jaya is the establishment of two Disaster Resilient Villages / Gampong located in the coastal area, namely Desa Lancang Kec. Bandar Baru and Desa Meuraksa district of Meureudu.